Intrapartum Ultrasonography for Labor Management - Malvasi, Antonio (Springer Berlin Heidelberg : Imprint: Springer, 2013)
During intrapartum obstetric care clinicians evaluate the fetal head position manually, either by abdominal or digital vaginal palpation. However, digital examination has been shown to be highly operator-dependent (subjective). Intrapartum ultrasound, on the other hand, seems to be reproducible and easy to learn. In crucial situations like obstructed labor, likely to require medical intervention, there really is a need for ultrasound assessment of birth progress and on the busy labor ward. This is the first book devoted entirely to intrapartum ultrasound for the management of labor. Experts in the field present their own experiences and summarize the published state of the art. The use of intrapartum ultrasonography in evaluation of the first and second stages of labor and diagnosis of the occiput posterior and transverse positions is clearly documented. Each situation is analyzed with the help of informative images, and invaluable tips and tricks are provided, showing how fetal head engagement and progression can be documented objectively. The importance of ultrasound in obstetrics risk management is also addressed. This book explains how intrapartum ultrasonography can be used to assess whether a safe natural delivery is likely or whether operative procedures are required. We hope it will be valuable for all professionals, physicians and midwifes alike, who care for labouring women.